My German Waka - Edein, Sam (Nigeria, 2022)
Sam was born and raised in Lagos, Nigeria. He graduated from university with a Bachelor of Science in Psychology. Since his university days, he has been a lover of side businesses. After graduating, he got a job as a teacher but continued his side hustle to provide for his basic needs. Desiring a better life for his future children, he decides to travel to Germany for his master's degree. On his arrival in Germany, Sam reveived some basic benefits he struggled for in Nigeria. However, he faced many challenges which includes a job delivering food by bicycle, even in the snow. Will Sam regret living Nigeria? Will he even graduate? Will he get a job that will allow him to remain in Germany?...
Keywords: Autobiography - Sam Edein; Non-Fiction; Travel - Greener pasture